2021
DOI: 10.30782/jrvm.937240
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of PCNA, MMP-9 and p53 in bovine ocular squamous cell carcinomas

Abstract: In this study, we aimed to compare and correlate the PCNA, MMP-9 and p53 expressions and differentiation degree of bovine ocular squamous cell carcinomas (BOSCCs) by immunohistochemical methods. The material of this study was composed of BOSCC biopsy samples taken from 30 cattle brought to our department. Tissue samples were fixed in 10% buffered formalin, processed routinely, embedded in paraffin, sectioned at 5 μm, and stained with hematoxylin & eosin in order to detect histopathological changes. Sections we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…In bovine fibropapillomas, our results show for the first time the overexpression of pro-and active forms of MMP-9, which may possess an important proteolytic activity directed to different ECM proteins; by immunohistochemistry, MMP-9 has been detected both in epithelial and fibroblast cells, which may indicate a possible role in cell proliferation and detachment from basement membrane through an intense digestion of ECM proteins. In addition, a similar pattern of MMP-9 expression was described in bovine ocular squamous cell carcinomas, a tumor type attributed to different factors such as papillomavirus and herpesviruses, where an increased MMP-9 expression compared to the control group was demonstrated (36). In a recent in vivo study, Altamura et al (37), showed that in feline oral squamous cell carcinoma cell lines, MMP-2 and−9 are expressed at gene and protein level, which in turn may suggest a contribution of feline oral squamous cell carcinoma cells to invasiveness, in agreement with studies on human oral squamous cell carcinomas, where MMPs expression may play a relevant role in determining the invasive phenotype of tumor cells (38).…”
Section: Discussionsupporting
confidence: 62%
“…In bovine fibropapillomas, our results show for the first time the overexpression of pro-and active forms of MMP-9, which may possess an important proteolytic activity directed to different ECM proteins; by immunohistochemistry, MMP-9 has been detected both in epithelial and fibroblast cells, which may indicate a possible role in cell proliferation and detachment from basement membrane through an intense digestion of ECM proteins. In addition, a similar pattern of MMP-9 expression was described in bovine ocular squamous cell carcinomas, a tumor type attributed to different factors such as papillomavirus and herpesviruses, where an increased MMP-9 expression compared to the control group was demonstrated (36). In a recent in vivo study, Altamura et al (37), showed that in feline oral squamous cell carcinoma cell lines, MMP-2 and−9 are expressed at gene and protein level, which in turn may suggest a contribution of feline oral squamous cell carcinoma cells to invasiveness, in agreement with studies on human oral squamous cell carcinomas, where MMPs expression may play a relevant role in determining the invasive phenotype of tumor cells (38).…”
Section: Discussionsupporting
confidence: 62%
“…This study expands beyond the viral focus to scrutinize host cellular components associated with BPV-induced squamous cell carcinoma. [13,[18][19][20][21][22] A panel of 24 markers and receptors, including crucial entities such as VEGF-C, EGFR, and TP53, was systematically analyzed to discern their interactions with various BPV variants. The outcomes of this analysis shed light on potential key players in the viral-host interplay, which can help development of targeted therapeutic interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the lack of significant interactions for BPV types 8, 10, and 12 with the screened markers suggests distinct characteristics and potential variations in their pathogenic mechanisms. [5,6,18] The analysis of 24 markers/receptors associated with BPV-induced squamous cell carcinoma provides a comprehensive overview of potential molecular targets. The higher affinity interactions observed for VEGF-C, EGFR, PDGFC, PDGFC-alpha, bFGF, GPC1, and FLG across multiple BPV variants indicate the significance of these markers in the context of viral pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations